Behcet's disease and pregnancy: what to expect?. (17th February 2018) - Orgul, Gokcen; Aktoz, Fatih; Beksac, Mehmet Sinan
Abstract: The relationship between Behcet's disease (BD) and pregnancy is only reported in limited number of studies. We retrospectively collected data of 26 women with BD diagnosis and their 66 pregnancies. We analysed patients according to disease activity, age at BD diagnosis, age at first/last pregnancy, obstetric history, obstetric complications, neonatal birthweight, associated foetal abnormalities and pregnancy-related complications. Sixteen miscarriages (24.2%), two intrauterine deaths (3%) and 48 live births (72.8%) were identified. Preterm labour was observed in 12 (24%) of 50 deliveries. Colchicine was used in six pregnancies, however, there was no drug treatment for BD in the remaining 59. There was a higher rate of preterm labour and low birthweight in patients using colchicine. BD was in remission in 60 (90.9%) of 66 pregnancies, and disease flared up only in six cases. In conclusion, BD patients with altered symptoms during pregnancy carry an increased risk of obstetric complications. IMPACT STATEMENT: What is already known on this subject: There are limited and conflicting data about the interaction between BD and gestation. What the results of this study add: Our findings indicated that patients who were in an active symptomatic phase of BD and were being treated with colchicine had an increased risk of preterm delivery and low birthweight. What the implications are of these findings for clinical practice and/or further research: Clinicians should consider increased obstetric complication risk among patients with active BD.